Prevalence of Intestinal Parasitic Infection in Baghdad City - Al-Taie, Lazem H. K. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: Intestinal parasites are endemic in many developing areas (WHO report 1998), and they considered as one of the most common tropical disease in developing countries ranges between 30-60 % .Patients and Methods: The present study is a survey to determine the prevalence of intestinal parasites in out and in patients of Al-karama hospital during the period from Jan 1999 to Nov. 2000. Stool samples examination was the test in establishing the results of the present study by direct microscopic examination. Q –square statistic test were used for evaluation the results.Results: Results of the present study reveled that the most affected group of patients’ with intestinal parasites, those with 11-20 years old (32%), protozoa percentage of infection were (18.56%) significantly more than helminthes with (2.45%). Males were more infected with intestinal parasites (44.18%) than females (28.96%). The highest infection rate with helminthes was recorded at the period between March and Jun.Conclusion: Infection rate in Baghdad City21.01,rotozoal18.56%,whichinclude E.histolytica12.14%,G.lambilia 4.9 % While helminth infection rate,2.45 %,include H.nana,1.17%Enter.vermicularis,0.38 %,Asca.lambricoidus0.37 %.Femal infection rate8.21 % more than male4.01 %.